Evaporation rates across a convective air boundary layer are dominated by diffusion. Issue 3 (27th March 2013) - Haghighi, E.; Shahraeeni, E.; Lehmann, P.; Or, D.
Key Points: The contributions of diffusion and advection to evaporative flux are quantified Diffusion dominates evaporation flux from partially wet surfaces Surface water content‐dependent evaporative resistance expression is developed Abstract : [1] The relative contributions of advection and diffusion to isothermal mass transfer from drying porous surfaces across a constant air boundary layer have been quantified. Analysis has shown that neglecting diffusion in longitudinal direction (often justified by large Peclet number) may lead to underestimation of evaporative mass losses from porous surfaces. Considering diffusion only from individual pores across a constant boundary layer accounts for most of the evaporation rates predicted by the full advection‐diffusion equation (ADE). The apparent decoupling between diffusion and advection, and the relatively small role of advection in flux generation (other than defining boundary layer thickness) greatly simplifies analytical description of drying surfaces. Consequently, evaporation rates from porous surfaces may be represented by superposition of readily‐available analytical diffusion solutions from discrete pores considering different patterns and spacing between surface pores. Results have been used to formulate a generalized top boundary condition for effective resistance to evaporation linking soil type, surface water content and boundary layer characteristic into a simple and physically based analytical expression.